The Christian Pastor - Oates, Wayne E. (Wayne Edward) (Philadelphia The Westminister Press, 1982)
A standard work in seminaries and a reliable guide for clergy in many denominations for over thirty years, The Christian Pastor has been revised to include up-to-date research on the role of pastors in contemporary life. In examining today's changing mini
Keywords: Pastoral theology. Pastoral psychology. Pastores